AN ASSESSMENT OF PARADIGM SHIFT IN PEOPLE’S PRIORITIES TOWARD INTERIOR DESIGNING OF SPACE DURING THE PANDEMIC OUTBREAK - Chugh, Damanpreet; Kaur, Prabhjot (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This investigation surfaces a thought of change in peoples’ priorities toward Interior design of space during the Pandemic outbreak. It re-examines the issues that influenced the change in the overall arrangement of a physical space. Five constructs were identified to validate the paradigm shift in peoples’ approach to dealing with spatial areas specifically in housing during the pandemic outbreak. The research study has shown a strong paradigm shift in the resident’s approach to the interior design of housing. The research study also discusses about the issues faced while stay at home during COVID-19, spatial layout during the pandemic, the utility of space during the pandemic, and targeting to achieve the required resilience through design implications. There were 404 participants considered in the structured questionnaire survey where the snowball sample technique to distribute among the policymakers, planners, architects, interior designers, and general citizens, from various residential areas in the Chandigarh Capital Region (CCR) i.e., Chandigarh, Mohali, and Panchkula who responded on varied issues faced during COVID-19. The outlook of people’s approach and interior design community to post-COVID has offered a new opportunity to re-look at the spatial arrangement of interior space. The residential dwelling units that were earlier considered for relaxation, safety, and storage are now considered for online classes, office work, play areas, recreation, and exercise areas. The post-COVID-19 era has changed the outlook of habitable space by providing a new thought process to visualize a spatial layout uniquely, which may further full-fill multiple interests at the same time. The research study not only focuses on residential dwelling units but also on the way people used their spaces and issues faced. Lack of proper spaces for classes, meetings, office works and other interested have changed the outlook people have perceive their spaces. And spaces during Covid-19 era have offered a fresh opportunity to rethink the design of any habitable space. Spaces with better adaptability, natural light, ventilation, and open spaces may have more potential of resilience than the space having poor ventilation, dingy and no open spaces. Clearly, in the research people of underprivileged were more susceptible to Covid infection and their recovery period may be longer as compared to the people living in planned and spaces residential dwelling units.